Perceived threat of technological disruption, job insecurity, and turnover intention in Egypt: a replication study - Mohamed Hossameldin Khalifa; Gamal Shehata (Cogent Psychology, 2025)
Prior research indicates that employee perceived threat of technological disruption (PTTD) positively affects turnover intention (TI) through the mediation of job insecurity (JI). Nonetheless, no prior research investigated the moderating effects of individual-level cultural orientations on the JI-mediated PTTD-TI link. To address this knowledge gap, this study draws on Conservation of Resources Theory and Cultural Dimensions Theory to examine the relationship between PTTD and TI, JI’s mediating role, and the moderating effects of individual-level collectivism and long-term orientation on JI’s mediating role, within the Egyptian private sector. Using online survey data from 348 full-time employees, regression results reveal that PTTD positively predicts TI, both directly and indirectly via JI. Additionally, the indirect effect is weakened by higher levels of collectivism. Limitations that should be addressed by future research include the cross-sectional design, limited generalizability due to a non-random private sector sample, self-report bias, and absence of organization-level moderators. Theoretical and practical contributions are outlined.